Contextualizing Kaili Cultural Symbols in the Oral Tradition of Mantra Balia in Central Sulawesi - Agustan; Dwi Septiwiharti; Rosmiani; Ade Asih Susiari Tantri (Mimbar Ilmu, 2025)
The purpose of this study is to discover and describe the contextualization of the Kaili ethnic group's balia mantra symbol in Palu, Central Sulawesi – Indonesia, which includes (1) contextualization of the form, meaning, and function of the balia mantra symbol in terms of tradition, (2) contextualization of the form, meaning, and function of the balia mantra symbol in terms of values, and (3) contextualization of the form, meaning, and function of the balia mantra symbol in terms of aesthetics. This research is an ethnographic study with an interdisciplinary approach. The research data consists of photographic documentation, recordings, and facts from the research location. Data collection activities were carried out using observation techniques, field notes, in-depth interviews, recordings, and documentation. Data analysis techniques used objective hermeneutics, divided into two procedures: (1) chain analysis and (2) detailed analysis. Data validity was ensured through triangulation at each stage of the research, research tools, and clarification of research findings with informants, namely the mantra practitioners known as Sando in the traditional ceremonies of the Kaili ethnic group. To authenticate the research results, focused group discussions and external auditors were conducted. The research findings are the form, meaning, and function of the balia mantra contextualized within the aspects of Kaili tradition, values, and aesthetics. Theoretically, this research strengthens the metapragmasemiotic approach by contextualizing the balia mantra within three aspects: tradition, values, and aesthetics. Practically, these findings are beneficial for universities related to linguistic education, which develop interdisciplinary knowledge by integrating metalinguistics, pragmatics, and semiotics into a metapragmasemiotic approach.